Influence of Synthesis Conditions on the Capacitance Performance of Hydrothermally Prepared MnO2 for Carbon Xerogel-Based Solid-State Supercapacitors - Vania Ilcheva; Victor Boev; Mariela Dimitrova; Borislava Mladenova; Daniela Karashanova; Elefteria Lefterova; Natalia Rey-Raap; Ana Arenillas; Antonia Stoyanova (Gels)
In this study, the potential to modify the phase structure and morphology of manganese dioxide synthesized via the hydrothermal route was explored. A series of samples were prepared at different synthesis temperatures (100, 120, 140, and 160 °C) using KMnO4 and MnSO4·H2O as precursors. The phase composition and morphology of the materials were analyzed using various physicochemical methods. The results showed that, at the lowest synthesis temperature (100 °C), an intercalation compound with composition K1.39Mn3O6 and a very small amount of α-MnO2 was formed. At higher temperatures (120–160 °C), the amount of α-MnO2 increased, indicating the formation of two clearly distinguished crystal structures. The sample obtained at 160 °C exhibited the highest specific surface area (approximately 157 m2/g). These two-phase (α-MnO2/K1.39Mn3O6) materials, synthesized at the lowest and highest temperatures, respectively, and containing an appropriate amount of carbon xerogel, were tested as active mass for positive electrodes in a solid-state supercapacitor, using a Na+-form Aquivion® membrane as the polymer electrolyte. The electrochemical evaluation showed that the composite with the higher specific surface area, containing 75% manganese dioxide, demonstrated improved characteristics, including 96% capacitance retention after 5000 charge/discharge cycles and high energy efficiency (approximately 99%). These properties highlight its potential for application in solid-state supercapacitors.